Regeneration of cultural landscape: inheritance and development of traditional eco-wisdom of polder landscape in Yangtze river region, China - Daixin, Dai (4D Journal of Landscape Architecture and Garden Art, 2018)
As an important form of land utilization and agricultural production along Yangtze River in Anhui Province, the polder constitutes the typical cultural landscape in the course of interactions between local residents and the great nature. The geographical conditions composed by the polders, the dams and the water network, the people and other living things in such an environment form the social ecological system (SES) together, which has not only constituted the local landscape with great regional characteristics, but played significant social and economic roles in history. Nowadays, the transform of land use results in confliction between the traditional eco-wisdom of polder landscape and the construction of new town in this area. To make reconnection, the paper summarizes the mechanism of the traditional polder landscape, which consists of three subsystems of stormwater management, land use and community. Based on that, regenerative strategies of planning and design are proposed in the case of Hangbu New Town in Shucheng County of Anhui Province. The conclusion can be drawn that the eco-wisdom of polder landscape still shows its strong vitality in proper planning strategies, and landscape regeneration should integrate economic, environmental and social efficiency together for the development of new towns.
Keywords: landscape architecture; landscape regeneration; ecological wisdom; polder landscape; stormwater control; ecological security pattern